VARIATIONS OF THE NUMBER OF WEAK AND STRONG EARTHQUAKES FOR 1997-1998 YEARS AND THEIR POSSIBLE PRECURSORS - Barliaeva T.V.; Pudovkin M.I.; Morozova A.L. (My University, 2001)
The earthquakes of various magnitudes (M ≥ 7.0, 4.0 ≤ M < 7.0) for the period from 1977 to 1998 are considered. A different recurrence of the number of strong and weak earthquakes is revealed. Variations of sunspot numbers, flare index, galactic cosmic ray fluxes, and Kp-index of geomagnetic activity are studied. From comparison of these characteristics with the distribution of the number of the earthquakes it may be assumed that the distinction in the characters of variations of weak and strong earthquakes is caused by the distinction in the solar and geomagnetic activity effect on occurrence of earthquakes of different magnitude.